The Knowledge Driven as Fundamental Analysis in The Geothermal Exploration Activity: Dieng Geothermal Field Study Area - Hardiyanto, Dwi Wahyu; Setianto, Agung; Harijoko, Agung (Faculty of Geography, Universitas Gadjah Mada, 2025)
Geothermal exploration activities involve a high degree of uncertainty and financial risk, thereby requiring exploration analyses that can support accurate decision-making. This study presents a geothermal exploration method for determining the Geothermal Potential Index (GPI) by integrating surface geological, geophysical, and geochemical data. The main problem addressed in this study is the testing of a method for conducting geothermal exploration by integrating multiple parameters. Accordingly, this research applies a knowledge-driven approach through the Analytic Hierarchy Process (AHP) to develop a tentative Geothermal Potential Index (GPI) model. The Analytical Hierarchy Process (AHP) serves as a reliable methodological framework for assessing the Geothermal Potential Index by integrating newly obtained and pre-existing data. By incorporating suitability analysis, identifying prospective resources, and formulating geothermal resource criteria, this approach establishes a solid basis for systematic evaluation during the geothermal exploration phase. The tentative model of the geothermal potential index (GPI) for the Dieng volcanic complex has been identified into five zones: Pagerkandang Zone, Siglagah Zone, Pangonan-Merdada Zone, Campursari Zone, and Pakuwaja Zone.